ETIKA KOMUNIKASI DALAM PENDIDIKAN: KAJIAN SURAT AL-KAHFI AYAT 60–70 - Hazrullah, Hazrullah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
The communication ethics in education contained in Surah Al-Kahf verses 60–70 are closely related to the story of the journey of Prophet Moses (Musa) and Al-Khidr. As the primary source of guidance for Muslims, the Qur'an not only contains teachings on faith and worship but also provides communication principles that are highly relevant to the educational process. The interaction between Prophet Moses and Al-Khidr illustrates a relationship between teacher and learner that is rich in ethical communication values, including respect, patience, humility, openness to knowledge, and the use of polite and educational language.This study employs a library research method using a thematic exegesis (maudhu'i) approach. The findings reveal several principles of communication ethics in education that can be implemented in the learning process, namely: (1) communication based on the intention to seek knowledge and truth; (2) humility (tawadhu') of learners toward educators; (3) patience in receiving and understanding knowledge; (4) the use of polite language that respects others; (5) the provision of explanations in a wise and gradual manner by educators; and (6) the importance of dialogue as a medium for knowledge transfer and character building. These values demonstrate that effective communication in education is not merely oriented toward the transmission of information but also toward the development of students' morals, character, and personality.